KOMUNIKASI DALAM MENANGGULANGI KORBAN PELECEHAN SEKSUAL DI USIA REMAJA (Studi Kasus pada Dinas Pemberdayaan Perempuan Provinsi Daerah Istimewa Yogyakarta) - Zahra Chaerani; Ardiyanto Wardhana (Jurnal Ilmu Komunikasi AKRAB, 2023)
ABSTRACTSexual harassment is a criminal act that not only attacks the victim physically, butalso psychologically. The victims of sexual harassment are not only among women;children are able to become victims of these criminal acts as well. The Special Region ofYogyakarta (or DIY) is one of the cities that has an increasing number of harassment andviolence every year. According to recorded data each year, the victims of sexualharassment and violence multiply. As of now, Indonesia has a constitution regulating theissue of sexual harassment implicitly in Article 28G and Article 28I. In Article 28G, everyonehas the right to self-protection, honor and dignity, as well as a sense of security andprotection from threats of fear to do or act something. Meanwhile, Article 28I states thateveryone has the right not to be tortured and receive discriminatory treatment. This studyused qualitative methods, which data collection techniques were obtained from interview,observation, and documentation. These data were subsequently written down in the field notes containing what was seen, heard, witnessed, experienced, and findings about whatwas encountered during the research and comprised data collection plans for the nextstep. The results achieved in this study were that DP3AP2 DIY carried out thecommunication strategy with persuasive communication methods.Keywords: Sexual harassment, DP3AP2 DIY, Communication strategy